Case Report: Suspected Case of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis Overlap Due to Ursodeoxycholic Acid - Shatavisa Mukherjee; Debajyoti Saha; Shreyashi Dasgupta; Santanu Kumar Tripathi (European Medical Journal, 2020)
Stevens-Johnson syndrome and toxic epidermal necrolysis are well-known severe cutaneous adverse reactions, with >100 medications previously implicated, most frequently sulfonamide antibiotics. Ursodeoxycholic acid (UDCA), normally present in human bile at a low concentration, is used for the treatment of various cholestatic disorders. Reports of UDCA causing cutaneous complications are, however, rare. The present report describes a suspected case of UDCA-induced Stevens-Johnson syndrome-toxic epidermal necrolysis overlap in a 24-year-old female, admitted with a whole-body maculopapular rash with oromucocutaneous ulceration and skin desquamation. The patient was managed with supportive care, including fluid and electrolyte replacement, corticosteroids, antibiotics, antihistamines, and intravenous Ig. Early identification, prompt intervention with effective care, and support are the key action points in these severe cutaneous adverse reactions.